Assessing the Relationship of Applied Force and Ablation Duration on Lesion Size Using a Diamond Tip Catheter Ablation System. (17th June 2021) - Verma, Atul; Schmidt, Megan M.; Lalonde, Jean-Pierre; Ramirez, David A.; Getman, Michael K.
Abstract : Background: Contact force has proven to be influential for lesion formation in power-controlled radiofrequency ablation. Lesion formation and morphology from a temperature-controlled diamond tip radiofrequency ablation catheter is not well described. We hypothesize that lesion formation from a temperature-controlled radiofrequency system is independent of applied force over short application durations. Methods: This study examined lesion depth, surface width, temperature, and ablation parameters of the DiamondTemp Ablation (Medtronic, Inc) system for ablation applications delivered with varying application duration (5, 10, and 15 s) and applied force (5, 10, and 30 g). Lesions from perpendicular radiofrequency applications were analyzed in a stepwise fashion from a computational model, thermochromic gel data (n=36), and porcine thigh preparation (n=231) experiments. Results: Varying applied force across each application duration consistently generated comparable lesion dimensions for each model. In the computational model, lesion depths from a 5 s application with 5, 10, and 30 g of applied force were similar (2.3, 2.6, and 3.0 mm, respectively). Also, the 5 s lesion depths in the gel model were consistent across applied force (5 g, 3.2±0.1 mm; 10 g, 3.5±0.1 mm; 30 g, 3.5±0.2 mm). In the thigh model, the 5, 10, and 30 g applied forces for 5 s created lesion depths of 3.1±0.5, 3.2±1.0, and 3.2±1.1 mm, respectively. For the 10 and 15 s durations, the lesion depth and width remained consistent for the 10 and 30 g applied forces. Increases in lesion depth and width, percentage of impedance reduction, minimum power, and maximum temperature were only significant when application duration increased (from 5 to 15 s). Conclusions: Lesion dimensions with the DiamondTemp Ablation temperature-controlled radiofrequency ablation system showed no marked change with increased applied force. Short application durations generated consistent lesion dimensions across computational, thermochromic gel, and thigh models.